South Asia Nutrition Knowledge Initiative: Abstract digest August 2024 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
In this third edition of the South Asia Nutrition Knowledge Initiative’s Abstract Digest, we present studies on global, regional, and country-specific evidence on various topics of nutrition. These include the impact of short birth intervals on child malnutrition in the Asia-Pacific region, a summary of lessons from program evaluations of food systems interventions for nutrition in South Asia, the effect of zinc supplementation in pregnant and lactating mothers in a three-country study, and a review of evidence on school meals, impact on nutrition, and their other evolving dimensions.